Influence of different compositions of fly ash as fluxing agent in porcelain - Alwi Kutty, Nur Azureen; Noh, Mohamad Zaky; Mayzan, Mohd Zul Hilmi; Durumin Iya, Sani Garba (Unique Research Publications, 2018)
Fly ash is alumina-silica waste products from the combustion of palm fiber and shells in the boiler which are collected at the multi-cyclone collectors where almost 3 million tonnes per annum being produced in palm oil industry in Malaysia. The aim of this paper is to investigate the replacement of feldspar by fly ash as potential fluxing agent in triaxial porcelain. Clay, feldspar, quartz and fly ash were mixed for 12 hours, pressed into pellets and sintered at 1250 ºC. The samples were measured according to the physical and mechanical properties. Microstructure study was done through SEM analysis. The optimum composition of fly ash was observed at 5 wt.% where the maximum compressive strength was achieved at 105.04 MPa and shows the decreasing results in volume shrinkage. SEM study shows intense interlocking between the primary and secondary mullite needles in glassy matrix which contribute in improving the strength of the porcelain at this composition. Therefore the substitution of fly ash is suitable as a fluxing agent in porcelain that improved its physical and mechanical properties.